BACTERIAL FLORA FROM DEAD-IN-SHELL JAPANESE QUAIL EMBRYOS AND THEIR DRUG RESISTANCE - Malmarugan, S; Jagadeeswaran, D; Rajendran, K; Dorairajan , N (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A study was carried out to determine the bacterial flora in dead in shell embryos from commercial quail hatcheries operating in Namakkal, Tamil Nadu. Among one hundred and twenty quail eggs failed to hatch at termination of incubation were collected, 58 isolates of bacteria comprising of Escherichia coli (29), Klebsiella spp (14 ), Staphylococcus spp (10), Salmonella spp (5) were cultured. The incubation period of Japanese quail eggs to hatch is 18 days. The level of bacterial contamination in quail eggs failing to hatch at 18th day of incubation was 70%. The antibiotic sensitivity pattern revealed that highest sensitivity were seen to Chloramphenicol (82.7%), Amoxycillin (70.6), Ciprofloxacin (60.3) and Gentamicin (48.27%) but were quite resistant to Oxytetracycline, Lincomycin and Co-trimaxazole.